Directional Blasting Technology of Slit Charge for Geological Disposal of High-Level Radioactive Waste. (3rd October 2018) - Man, Ke; Liu, Xiaoli; Wang, Ju; Wang, Xiyong
Abstract : Based on the slit charge technology, the blasting progress and the blasting theory have been studied in detail. Combined with the high-level radioactive waste geological disposal, in which the excavation damaged zone of the surrounding rock is required as small as possible, the testing of the Beishan exploration tunnel (BET) has been studied, and the blasting parameters have been designed using the slit charge technology. Theoretically, the rock failure criterion has been proposed, which adopted the dynamic mechanical parameters, such as the dynamic compress strength, dynamic tensile strength, dynamic modulus, dynamic passion ratio, dynamic fracture toughness, and dynamic stress intensity factor. Furthermore, the blasting test has been carried out under the same tunnel face with left and right sides simultaneously, and it can be found that the blasting effect with the slit charge technology is better than another side, which verified the useful and scientific meaning of this technology. It should be noticed that the blasting method includes numerous blasting parameters, which interact with each other. Those blasting parameters obtained just limited the slit charge, and the result and the theoretical knowledge could be applied to the blasting and excavation of the deep geoengineering and HLW geodisposal.